South African consumer sentiment towards marketing: A longitudinal analysis - C. Boshoff; S. M. Van Eeden (South African Journal of Business Management, 2001)
A constant interaction occurs between the firm, its markets and the variables in the business environment. This dynamic interaction ensures that changes in the environment continuously exert an influence on consumer attitudes and sentiment and how consumers react to and perceive the marketing of products and services.The primary objective of this longitudinal study is to measure South African consumer sentiment towards marketing and to compare the results with previous studies done in 1990 and 1994. Secondary objectives include an investigation to establish to what extent this sentiment towards marketing is influenced by demographic variables.Although the marketing index decreased during the period 1990 to 1994, it improved dramatically during the period 1994 to 1999. In contrast to the previous studies it was established that demographic factors had no significant influence on the sentiment towards marketing in this study.As it is generally acknowledged that attitudes influence actual buying behaviour, marketers need to be aware that attitudes and sentiment toward marketing and marketing activities can change over time and proactive steps need to be taken to ensure that sentiment remains positive regardless of the changes in the external environment.
Keywords: 650